Primary Repair of Extensive Rectal Injury during Urethroplasty in Children Without Bowel Preparation: Report of Two Cases - Basiri, Abbas; Dadpour, Mehdi (Urology Journal, 2020)
Today, there are several methods to repair colon and rectal injury such as primary repair, stoma, resection with anastomosis and damage control only. To our best knowledge, there is no definite method published in literature about iatrogenic rectal injury during perineal urethroplasty in children. Here, we explain two 10 and 12-year old boys with iatrogenic rectal injury during perineal urethroplasty who underwent primary repair. Based on our experience, primary repair of rectum in such condition is feasible, successful and can be a good choice to avoid placing colostomy and secondary repair. Keywords: complication; rectal injury; perineal urethroplasty; primary repair